Anticancer Quinolinol Small Molecules Target Multiple Pathways to Promote Cell Death and Eliminate Melanoma Cells Resistant to BRAF Inhibitors - Xinjiang Wang; Rati Lama; Alexis D. Kelleher; Erika C. Rizzo; Samuel L. Galster; Chao Xue; Yali Zhang; Jianmin Wang; Jun Qu; Sherry R. Chemler (Molecules)
Small molecule inhibitors that target the E3 ligase activity of MDM2-MDM4 have been explored to inhibit the oncogenic activity of MDM2-MDM4 complex. MMRi62 is a small molecule that was identified using an MDM2-MDM4 E3 ligase-based high throughput screen and a cell-death-based secondary screen. Our previous studies showed that MMRi62 promotes MDM4 degradation in cells and induces p53-independent apoptosis in cancer cells. However, MMRi62 activity in solid tumor cells such as melanoma cells, especially in BRAF inhibitor resistant melanoma cells, have not been explored. Although its promotion of MDM4 degradation is clear, the direct MMRi62 targets in cells are unknown. In this report, we show that MMRi62 is a much more potent p53-independent apoptosis inducer than conventional MDM2 inhibitors in melanoma cells. A brief structure-activity study led to development of SC-62-1 with improved activity. SC-62-1 potently inhibits and eliminates clonogenic growth of melanoma cells that acquired resistance to BRAF inhibitors. We developed a pair of active and inactive SC-62-1 probes and profiled the cellular targets of SC-62-1 using a chemical biology approach coupled with IonStar/nano-LC/MS analysis. We found that SC-62-1 covalently binds to more than 15 hundred proteins in cells. Pathways analysis showed that SC-62-1 significantly altered several pathways including carbon metabolism, RNA metabolism, amino acid metabolism, translation and cellular response to stress. This study provides mechanistic insights into the mechanisms of action for MMRi62-like quinolinols. This study also suggests multi-targeting compounds like SC-62-1 might be useful for overcoming resistance to BRAF inhibitors for improved melanoma treatment.